Actie van ambtenaren tegen 3,5 % loonsverlaginging. Voor het ministerie van binnenlandse zaken - Singels, Han,
Actie van ambtenaren tegen 3,5 % loonsverlaginging. Voor het ministerie van binnenlandse zaken.